The Concept of Pain in Children Attending Primary School: Implications for School-Based Pain Education - Talita Odendaal; Ina Diener; Quinette Abegail Louw; Dawn Verna Ernstzen (Pain Research and Management)
Conclusions: Participants had a developing concept of pain that was partially aligned with contemporary pain science. Participants had pain knowledge strengths and gaps that can be used to develop a tailored school-based pain education intervention for them. There were indications that contextual factors may have influenced the participants’ concept of pain. Further studies to explore socioenvironmental factors that influence pain knowledge in children are recommended.